1993
DOI: 10.1111/j.1471-4159.1993.tb13384.x
|View full text |Cite
|
Sign up to set email alerts
|

Ammonium Injection Induces an N‐Methyl‐d‐Aspartate Receptor‐Mediated Proteolysis of the Microtubule‐Associated Protein MAP‐2

Abstract: We have shown previously that chronic hyperammonemia increases, in brain, the polymerization of microtubules that is regulated mainly by the level and state of phosphorylation of microtubule-associated protein 2 (MAP-2). Activation of the N-methyl-D-aspartate (NMDA) receptor dephosphorylates MAP-2. Because we have found that acute ammonia toxicity is mediated by the NMDA receptor, we have tested the effect of high ammonia levels on MAP-2 in brain. Microtubules isolated from rats injected intraperitoneally with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 27 publications
1
38
0
Order By: Relevance
“…and adult brain. This idea is supported by dynamic regulation of MAP2 expression and its involvement in dynamic changes in neuronal morphology caused by excitotoxins (Siman and Noszek, 1988;Bigot et al, 1991;Felipo et al, 1993;Arias et al, 1997;Faddis et al, 1997;Hoskison and Shuttleworth, 2006;Hoskison et al, 2007), traumatic brain injury (Taft et al, 1992;Folkerts et al, 1998), or focal ischemia (Pettigrew et al, 1996;Schwab et al, 1998). In addition, manipulations of synaptic activity alter the immunoreactivity for MAP2 in dendrites (Hendry and Bhandari, 1992;Steward and Halpain, 1999;Vaillant et al, 2002), further suggesting that synaptic activity either directly or indirectly regulates MAP2 expression.…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…and adult brain. This idea is supported by dynamic regulation of MAP2 expression and its involvement in dynamic changes in neuronal morphology caused by excitotoxins (Siman and Noszek, 1988;Bigot et al, 1991;Felipo et al, 1993;Arias et al, 1997;Faddis et al, 1997;Hoskison and Shuttleworth, 2006;Hoskison et al, 2007), traumatic brain injury (Taft et al, 1992;Folkerts et al, 1998), or focal ischemia (Pettigrew et al, 1996;Schwab et al, 1998). In addition, manipulations of synaptic activity alter the immunoreactivity for MAP2 in dendrites (Hendry and Bhandari, 1992;Steward and Halpain, 1999;Vaillant et al, 2002), further suggesting that synaptic activity either directly or indirectly regulates MAP2 expression.…”
mentioning
confidence: 62%
“…Among a number of regulatory mechanisms controlling MAP2 function (see review, Sánchez et al, 2000), changes in calcium signaling, especially rises in intracellular calcium concentration ([Ca 2+ ] i ), have been most extensively studied following manipulations of synaptic inputs. Excessive glutamate receptor stimulation induced by physiological stimulation or exposure of glutamate or agonists of its receptors causes dendritic injury and/or MAP2 loss (Siman and Noszek, 1988;Bigot et al, 1991;Felipo et al, 1993;Arias et al, 1997;Faddis et al, 1997;Steward and Halpain, 1999;Swann et al, 2000;Vaillant et al, 2002). Recent studies in hippocampal slices further demonstrated that these changes are calcium-dependent (Hoskison and Shuttleworth, 2006;Hoskison et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This effect was reversed by the PKC activator 12-0-tetradecanoyl-13.phorbol-acetate (TPA), which confirms the involvement of PKC [3]. It has been claimed that PKC is sensitive to thiol-disulflde exchange; hence, its activity may be sensitive to the redox state of the cellular environment [4].…”
Section: Introduction It Has Been Recently Reported That I-(s-isoquinmentioning
confidence: 63%
“…was obtainccl from the American Type Culture Collection, Rockvillr, MD, and grown at 37°C in Eagle's minimum csscntial medium. supplemented with 10% feral bovine serum, 100 IU penicillin/ml, and 1OOyg of streptomycin/ml as previously described [2,3]. H7, TPA, staurosporinc and sphingosine were from Sigma Chemical Co. (St. Louis, MO).…”
Section: Methodsmentioning
confidence: 99%
“…L-carnitine, which protects rats against glutamate toxicity, also prevented MAP-2 degradation by cytosolic Ca 2+ -dependent protease, which has been identified tentatively as calpain I (Felipo et al 1993). Kuzin and Kolesnikova (1999) found that L-carnitine after cerebral hypoxia inhibits development of apoptosis, limits the area of damage and restores structure of nervous tissue.…”
Section: Discussionmentioning
confidence: 99%